Digital Bureaucracy and Public Trust in Indonesia: A Governance Analysis of EGDI Trends and Regional Disparities - Pratama, Muhammad Anzarach; Malizal, Zelynda Zeinab (Indonesian Scientific Publication, 2025)
This study explores Indonesia’s e government development between 2016 and 2024, analyzing its implications for administrative efficiency and public trust. It assesses trends in the E Government Development Index (EGDI), emphasizing the sub-indices of Online Service Index (OSI), Telecommunication Infrastructure Index (TII), and Human Capital Index (HCI). The research also examines regional disparities, digital participation, and the influence of service quality on citizen trust. The methodology combines quantitative analyses of EGDI scores with governance metrics and citizen trust indicators, supplemented by regional comparative analysis and case studies. Correlational and regression models were used to evaluate the impact of digital service quality on trust, while qualitative data from literature and case studies offered contextual insights into implementation gaps. Findings show that improvements in OSI, TII, and HCI have contributed to better public service delivery and enhanced public trust. However, regional disparities persist, particularly between urban and rural areas, affecting digital participation and service equity. Trust in government is significantly shaped by service reliability, transparency, and inclusiveness. While EGDI offers a useful performance proxy, it does not fully capture service satisfaction or governance responsiveness. The study concludes that to ensure inclusive and effective digital governance, Indonesia must integrate citizen centric service design, institutionalize transparency through open data, and bridge infrastructure gaps through policy harmonization. These steps are essential to promote democratic accountability, administrative efficiency, and sustainable public trust in the digital era.